28PCNAs concordance between CRC-PDOs and the original tissue reveals relevant oncogenic pathways alterations. (7th November 2019) - Papaccio, F; Valiente, F G; Gutierrez-Bravo, M F; Cabeza-Segura, M; Gambardella, V; Huerta, M D S; Martinez-Ciarpaglini, C; Alfaro-Cervello, C; Rentero-Garrido, P; Zúñiga-Trejos, S; Rosello Keranen, S; Fleitas, T; et al.
Abstract: Background: Colorectal cancer (CRC) patients derived organoids (PDOs) are 3D in vitro primary culture representing an increasingly used model for precision medicine. Besides somatic mutations, CRC is characterized by certain levels of copy number alterations (CNAs): somatic gain or loss of DNA sections, which can include oncogenes or tumor suppressors. We aimed to analyze CNAs concordance between CRC-PDOs and the original tumor tissue. Methods: Primary or metastatic CRC tissues have been obtained from patients who underwent surgery. Tissue has been washed and incubated with antibiotics. After mechanical and enzymatic digestion, free cells have been seeded in Matrigel with proper medium. Development of organoids has been observed the day after seeding. Organoids have been passaged, expanded and stored in liquid nitrogen to constitute a biobank. After reaching appropriate volume, DNA from PDOs and matched fresh tumor tissue has been extracted. Next generation sequencing (NGS) has been performed with an in-house customized cancer specific 85-gene panel. Cytoscan-HD (Thermo-Scientific) array has been performed according to manufacturer protocol. Data analysis has been performed with Chromosome Analysis Suite (Applied Biosystems v4.0). Results: NGS analysis showed high level concordance between PDOs and matched tumor tissue. Cytoscan-HD analysis was feasible and effective with PDOs. Results revealed good concordance between PDOs and original patient tissue. PDOs maintain mosaicism indicating certain level of heterogeneity. Among the CNAs detected we were able to detect alterations of interest, such as loss of regions including SMAD2, SMAD4, MTOR, CASP9, EPHB2, RUNX3, RSPO1, TIE1, JAK1, TGFBR3, VCAM1, PIK3C3 and amplification of regions containing NOTCH2L, CDH1L, MUC1, NTRK1, MAPKAPK2, TGFB2, TP53BP2, PARP1, WNT3A, ARID4B, AKT3, CDH4, AURKA. Conclusions: In addition to mutation profile, CRC-PDOs CNAs pattern reflects that of the original patient tissue, allowing to capture genomic alterations other than sequencing. Further validation is needed. Legal entity responsible for the study: INCLIVA Biomedical Research Institute. Funding: Instituto de Salud Carlos III, Rio Hortega contract, Joan Rodes Contract, ESMO Translational Research Fellowship Programme. Disclosure: A. Cervantes: Advisory / Consultancy, Speaker Bureau / Expert testimony, Research grant / Funding (institution): Merck Serono; Advisory / Consultancy, Speaker Bureau / Expert testimony, Research grant / Funding (institution): Roche; Advisory / Consultancy, Research grant / Funding (institution): Beigene; Advisory / Consultancy, Research grant / Funding (institution): Bayer; Advisory / Consultancy, Speaker Bureau / Expert testimony, Research grant / Funding (institution): Servier; Advisory / Consultancy, Research grant / Funding (institution): Lilly; Advisory / Consultancy, Research grant / Funding (institution): Novartis; Advisory / Consultancy, Research grant / Funding (institution): Takeda; Advisory / Consultancy, Research grant / Funding (institution): Astellas; Advisory / Consultancy: Pierre Fabre; Research grant / Funding (institution): Genentech; Research grant / Funding (institution): Fibrogen; Research grant / Funding (institution): Amcure; Research grant / Funding (institution): Sierra Oncology; Research grant / Funding (institution): AstraZeneca; Research grant / Funding (institution): MedImmune; Research grant / Funding (institution): BMS; Research grant / Funding (institution): MSD; Speaker Bureau / Expert testimony: Amgen; Speaker Bureau / Expert testimony: Foundation Medicine. All other authors have declared no conflicts of interest.